St. Petersburg dialogues, or, Conversations on the temporal government of Providence - Maistre, Joseph Marie, comte de, 1753-1821 (McGill-Queens University Press, 1993)
Analisa a providência divina, o bem e o mal, o sacrifício e a teoria cristã sobre o sacrifício humano.